Struktur Modal: Analisis Faktor-faktor pada Perusahaan Manufaktur BEI - Azhar, Ibnu; Azhar, M. Karya Satya (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to analyze the factors that affect the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. The factors tested in this study include ownership structure, company size, non-debt tax shield, tangibility, and growth. The population in this study was food and beverage subsector manufacturing companies in the observation year from 2015 to 2018 which amounted to 25 companies, using purposive sampling sample selection techniques so that as many as 13 companies were obtained. This study used multiple linear regression analysis preceded by testing classical assumptions then ending with hypothesis testing. The results of the study partially show ownership structure, company size, non-debt tax shield and tangibility have a significant effect on capital structure, while growth does not affect capital structure.